Proteomic characterization of MET-amplified esophageal adenocarcinomas reveals enrichment of alternative splicing- and androgen signaling-related proteins - Bastian Grothey; Su Ir Lyu; Alexander Quaas; Adrian Georg Simon; Jin-On Jung; Wolfgang Schröder; Christiane J. Bruns; Lars M. Schiffmann; Felix C. Popp; Thomas Schmidt; Karl Knipper (Cellular and Molecular Life Sciences)
Abstract Background Esophageal adenocarcinomas (EACs) represent an evolving tumor entity with high mortality rates. MET amplification is a recurrent driver in EACs and is associated with decreased patient survival. However, the response to MET inhibitors is limited. Recent studies have identified several mechanisms that lead to resistance against MET inhibitors in different tumor entities. Nonetheless, a characterization of additional vulnerable targets beyond MET has not been conducted in MET-amplified EACs. Methods In this study, we determined the MET amplification status in a cohort of more than 900 EACs using fluorescence in situ hybridization (FISH) and compared the proteomes of MET-amplified (n = 20) versus non-amplified tumors (n = 39) by mass spectrometry. Results We identified a phenotype, present in almost all MET-amplified tumors, which shows an enrichment of alternative RNA splicing, and androgen receptor signaling proteins, as well as decreased patient survival. Additionally, our analyses revealed a negative correlation between MET expression and patient survival in MET-amplified EACs, indicating biological heterogeneity with clinical relevance despite the presence of MET amplification as the predominant oncogenic driver. Furthermore, quantitative immunohistochemical analysis of the inflammatory tumor microenvironment showed that an increased percentage of M2 macrophages is associated with lower overall survival in MET-amplified EACs. Conclusions Our results provide valuable insights into possible new therapeutic approaches for MET-amplified EACs for further research.